EFEK CEO OVERCONFIDENCE TERHADAP PENGAMBILAN RISIKO LIKUIDITAS BANK KOMERSIL DI INDONESIA - Darus Altin; Ridwan Nurazi; Fitri Santi; Syaiful Anwar (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2022)
This study proves the effect of CEO Overconfindence on liquidity risk taking of commercial banks in Indonesia. The sample used was 53 banks with observations of 1007 banks in Indonesia from 2000-2018. The banks in Indonesia are divided into four classifications of BUKU (Commercial Banks Based on Business Classification). The findings of this study prove that CEO Overconfidence has a positive effect on liquidity risk in BUKU 1 and BUKU 2 banks and the smaller bank size in terms of total assets makes CEOs tend to be overconfident and bolder in taking bank liquidity risks. Our study is important for the development of a liquidity risk-taking model for Indonesian banks.Ã‚Â Keywords: CEO Overconfidence, LDR, BUKU